What Prompted the Adoption of Self-Protective Behaviors in Response to COVID-19? Evidence From Women Living in the Rural Areas of Western China - Ye, Ruixue; Wu, Yuju; Sun, Chang; Wang, Qingzhi; Mao, Yuping; Chang, Wei; Zhou, Huan (Frontiers in Public Health, 2022)
Background Self-protective behaviors, such as handwashing and mask-wearing, are effective to reduce the spread of coronavirus disease (COVID-19), but few studies have focused on women living in rural areas who bear the brunt of the impacts of the pandemic due to their economic and social vulnerabilities. This study explores what prompted the adoption of self-protective behaviors in response to COVID-19 among women living in rural areas of western China. Methods The study sample consisted of 1,524 women from 116 townships across 10 counties in rural western China. We collected data in May and August 2020 on women's socioeconomic characteristics, exposure to COVID-19-related information, psychological response to COVID-19, and adoption of self-protective behaviors. Structural equation modeling (SEM) analyses were conducted to analyze the relations among the variables. Results During the lockdown, 1,221 (80.12%) of the 1,524 women in the study sample reported wearing a mask every time when they went outside and 1,021 (66.99%) reported handwashing with soap every time after they came home. Perceived efficacy had the strongest association with self-protective behaviors (β = 0.38; p < 0.001). Receiving public health guidance (β = 0.18; p < 0.001) was indirectly associated with more self-protective behaviors via greater perceived efficacy. Higher socioeconomic status was also directly associated with increased adoption of self-protective behaviors (β = 0.24; p < 0.001). Other variables, such as receiving surveillance and risk information, communication channels, perceived risks, and fear, were indirectly associated with the adoption of self-protective behaviors with smaller effect sizes (all β were lower than 0.10). Conclusions Not all women were able to adopt self-protective behaviors, such as mask-wearing and handwashing, during the COVID-19 pandemic in western China. To further encourage behavioral changes in response to public health crises, the government should develop clear and actionable guidelines and adopt targeted health communication strategies to reach the most disadvantaged groups of society. These findings may inform tailored responses to COVID-19 in other low- and middle-income countries.